Examining the Role of Nuclear Energy and Financial Development on Biodiversity Risk in France: New Evidence from NARDL - Foday Joof; Ahmed Samour; Turgut Tursoy; Marlina Widiyanti (Universitas Pasundan, 2023)
This study aims to investigate the nonlinear effect of nuclear energy, economic complexity, and financial development on biodiversity in France using the NARDL. Unlike other traditional proxies of ecological quality (CO2 and EF), this study utilized the “Biodiversity habitat index”. The analysis revealed that positive shocks in nuclear energy led to sustainable biodiversity in France. Moreover, negative shocks from nuclear energy led to biodiversity losses both in the short and long term. Moreover, financial development and economic complexity were found to exhibit favorable conditions for biodiversity in the long term. Contrarily, economic growth accelerates biodiversity loss in France. Policymakers should endeavor to promote investments in nuclear energy, green finance, and implementation of climate-related risk management frameworks.